Review of the application of phase change material for heating and domestic hot water systems. (February 2015) - Sharif, M.K. Anuar; Al-Abidi, A.A.; Mat, S.; Sopian, K.; Ruslan, M.H.; Sulaiman, M.Y.; Rosli, M.A.M.
Abstract: Heating and domestic hot water (DHW) systems account for 75% of energy consumption in residential, commercial, and industrial sectors. Furthermore, thermal energy storage strongly reduces energy consumption. Storage devices of thermal energy from phase change material (PCM) are essential in solar thermal and waste heat energy technologies that match energy supply to demand and enhance their thermal performance. The storage of PCM thermal energy is more beneficial than sensible energy storage because of its high density of storage energy per unit volume/mass. This review presents previous works on thermal energy storage as applied to DHW and heating systems. PCM has been used in different parts of heating networks and DHW systems, including solar collectors, storage tanks, packed beds, and duct networks. Researchers have also investigated the application of PCM in heating and DHW systems to reduce greenhouse gas emission and electrical power consumption. Hence, PCM thermal energy storage is expected to lower cost and the volumes of heating and DHW systems.